Cardiovascular risk factors from diagnosis in children with type 1 diabetes mellitus: a longitudinal cohort study. Issue 1 (4th October 2019) - Jones, Stephanie; Khanolkar, Amal R; Gevers, Evelien; Stephenson, Terence; Amin, Rakesh
Abstract : Background: For childhood onset type 1 diabetes (T1D), the pathogenesis of atherosclerosis is greatly accelerated and results in early cardiovascular disease (CVD) and increased mortality. However, cardioprotective interventions in this age group are not routinely undertaken. Aims: To document prevalence of cardiovascular risk factors from diagnosis of childhood T1D and their relationship with disease duration and ethnicity. Methods: Routinely collected clinical records for 565 children with T1D were retrospectively analyzed. Data were collected from diagnosis and at routine check-ups at pediatric diabetes clinics across Barts Health National Health Service Trust. Age at diagnosis was 8.5 years (0.9–19.4). Mean follow-up 4.3 years (0–10.8). 48% were boys and 60% were non-white. Linear longitudinal mixed effects models were used to evaluate relationships between risk factors and diabetes duration. Results: CVD risk factors were present at first screening; 33.8% of children were overweight or obese, 20.5% were hypertensive (elevated diastolic blood pressure (BP)) and total cholesterol, low-density lipoprotein-cholesterol and high-density lipoprotein-cholesterol were abnormal in 63.5%, 34.2% and 22.0%, respectively. Significant associations between diabetes duration and annual increases of body mass index (0.6 kg/m 2 ), BP (0.1 SD score) and lipids (0.02–0.06 mmol/L) were noted. Annual increases were significantly higher in black children for BP and Bangladeshi children for lipids. Bangladeshi children also had greatest baseline levels. Conclusions: CVD risk factors are present in up to 60% of children at diagnosis of T1D and increase in prevalence during the early years of the disease. Commencing screening in younger children and prioritizing appropriate advice and attention to ethnic variation when calculating risk should be considered.